Penggunaan Media Instagram dalam Mempertahankan Budaya Lokal Kain Jumputan Kota Palembang (@bebajoemputan) - Agustini, Meli; Syarifudin, Achmad; Muslimin (Indonesian Journal Publisher, 2024)
Social media is a type of cyber media whose presence is in line with the development of information technology, especially the internet. Social media is present and changing the communication paradigm in today's society. Communication is not limited by distance, time or space, it can occur anywhere, at any time, without having to meet face to face. This social media not only contains information that is accessed by the public (netizens) but on the other hand, anyone can produce content and distribute it. Social media is also a place to build one's self-image in front of other people. This building of popularity and existence is a matter of satisfaction for most people. Instagram is one of the social media that is popular with Indonesians. . Instagram is a social media application that is used to share photos and videos. Instagram is a promising tool for various accounts such as entertainment and online shops. And promotional events. The need for information is basic for humans today. Humans rely on information to fulfill various needs such as increasing knowledge, improving skills, reducing uncertainty, gaining satisfaction and so on. Bebajoemputan Palembang shop promotes its products using Instagram to maintain the existence of local jumputan cloth culture and encourage local brands to develop rapidly. Jumputan cloth has high historical and cultural value, witnessing the history of Palembang for hundreds of years. Jumputan is a way of applying decoration to textiles by tying certain parts together and then dipping them in dye.